Gambaran Kisah Inspiratif Dengan Menggunakan Majas Dan Citraan Dalam Puisi “If” Karya Rudyard Kipling - Novira Kania Hermiliany (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
From the various studies that have been carried out, it can be observed that study on figurative language with stylistic studies has been studied extensively. Although there are many studies on figure of speech and imagery with stylistic studies, the writer believes that the same study still needs to be done. The writer does this to complement and add to previous stylistic studies. Relevant theories are used in this study to assist the results of the analysis to be obtained. The purpose of this study is to describe an inspiring story using various figures of speech and imagery contained in the poem "If" by Rudyard Kipling. “If” is an inspirational poem that gives advice on how one should live one's life. The poem takes the reader through various ways in which the reader can overcome difficulties in one's life. Throughout the poem, the speaker provides the reader with multiple scenarios, both positive and negative, along with glimpses of how one should behave. The approach used in this study is a stylistic approach. The method used in this study is descriptive analysis method with semiotics. This study data is descriptive data, namely data in the form of words, phrases, and sentences in the poem entitled "If" by Rudyard Kipling. The results of this study proved the existence of the use of figure of speech and imagery. Based on data analysis, the following results were obtained. First, the most dominant figure of speech was the personification figure of speech in the second stanza. Second, the dominant imagery that appears in the poem "If" by Rudyard Kipling was the image of motion and sight. The most dominant image is the image of motion. Motion imagery described something not actually moving, or an image of motion in general. Motion imagery was used to further liven up the image in the poem.